Home Eazy: Flexible Home Assistant Solution with Easy Access - Khairani Syahbana; Mera; Nor Anisa (INSTALL: Information System and Technology Journal, 2025)
Home Eazy is an innovative startup that focuses on providing on-demand household assistant services. Through this startup, users can request household assistants for various household tasks through a digital application. This study aims to evaluate Home Eazy's business potential, operational effectiveness, and marketing strategy. The findings show that this business model has significant opportunities, especially due to the lack of local competitors. As the first startup in the household service sector, Home Eazy has the potential to build a strong brand image among consumers, capture a large market share ahead of competitors, create new jobs, generate substantial profits, collect valuable data early, build new market infrastructure, and attract investor support. The service is accessible anytime and anywhere, so users can easily get household help through digital devices such as smartphones or computers.